A highly selective and sensitive photoinduced electron transfer (PET) based HOCl fluorescent probe in water and its endogenous imaging in living cells. Issue 51 (3rd June 2016) - Liang, Lijuan; Liu, Chang; Jiao, Xiaojie; Zhao, Liancheng; Zeng, Xianshun
Abstract : A probe based on the phenothiazine–acridine orange conjugate (Ptz–AO) has been designed and synthesized for the sensitive and selective detection of HOCl. Abstract : A probe based on the phenothiazine–acridine orange conjugate (Ptz–AO) has been designed and synthesized for the sensitive and selective detection of HOCl. Ptz–AO has excellent properties, including pH-independence of fluorescence, high resistance to photobleaching, and response in real time. The value of Ptz–AO was confirmed by exogenous, endogenous and the real-time imaging of HOCl in vitro using a fluorescence microscope.